2021
DOI: 10.1038/s41598-021-02248-5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of quercetin therapeutic targets for Alzheimer disease and type 2 diabetes mellitus

Abstract: Quercetin has demonstrated antioxidant, anti-inflammatory, hypoglycemic, and hypolipidemic activities, suggesting therapeutic potential against type 2 diabetes mellitus (T2DM) and Alzheimer’s disease (AD). In this study, potential molecular targets of quercetin were first identified using the Swiss Target Prediction platform and pathogenic targets of T2DM and AD were identified using online Mendelian inheritance in man (OMIM), DisGeNET, TTD, DrugBank, and GeneCards databases. The 95 targets shared among querce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 45 publications
(43 reference statements)
0
25
0
1
Order By: Relevance
“…Quercetin reduces the concentration of blood glucose levels, preserves the function of islets cells, number of β cell numbers in model rats and mice with diabetes. Experiments show that quercetin intake has a positive impact to prevent and treat the occurrence of diabetes mellitus [62,69].…”
Section: Diabetesmentioning
confidence: 99%
“…Quercetin reduces the concentration of blood glucose levels, preserves the function of islets cells, number of β cell numbers in model rats and mice with diabetes. Experiments show that quercetin intake has a positive impact to prevent and treat the occurrence of diabetes mellitus [62,69].…”
Section: Diabetesmentioning
confidence: 99%
“…( Deshpande et al, 2008 ; Prasad et al, 2016 ). VEGFA and JUN were identified as the central players in diabetic nephropathy ( Oltean et al, 2015 ; Wang et al, 2021 ) and Alzheimer’s disease ( Zu et al, 2021 ) whereas, VEGFA was associated with diabetic retinopathy ( Bucolo et al, 2021 ), cardiac autonomic neuropathy ( Ravichandran et al, 2019 ), and non-alcoholic fatty liver disease-hepatocellular carcinoma ( Shen et al, 2022 ). Each hub gene plays a vital and diverse role in the pathways and biological processes.…”
Section: Discussionmentioning
confidence: 99%
“…What's more, quercetin increased the expression of brain-derived BDNF and SIRT1 protein, which indicated a neuroprotective role of quercetin (Hu et al, 2020). A recent study aimed to identify the potential target of quercetin suggested that quercetin may have a synergic effect on DM and AD by targeting MAPK pathways (Zu et al, 2021).…”
Section: Quercetinmentioning
confidence: 99%